Editorial - Rita Niemann (Perspectives in Education, 2013)
From text: This edition of Perspectives in Education seeks to add to education discourses by exploring experiences in both school and higher education settings. I was struck by the fact that most of the papers challenged hegemonic systems and how teaching and subsequently, effective learning, can contribute to the development of agency to address pertinent social issues.